Needs analysis of an augmented reality-based picture story module to improve social awareness and reading literacy among elementary school students - Abdulah Abdulah (Privietlab, 2025)
This study aimed to reveal students' needs for Augmented Reality-based picture story modules to improve reading literacy and social awareness. The subjects of this study were 30 fifth-grade students from SD S Muhammadiyah Sungailiat. Data collection techniques included interviews, observations, questionnaires, and documentation. Qualitative research data were analyzed through three stages: data reduction, data presentation, and conclusion drawing. Quantitative data from the needs questionnaire were analyzed using a percentage formula to determine the level of students' needs for AR-based picture story modules. Furthermore, to maintain data validity, this study used source and technical triangulation techniques. The results of this study indicate that the need for AR-based picture story modules is high. The percentage range of needs for Augmented Reality-based picture story modules is at 73.33% - 87.50%. These findings are seen in each indicator, namely the reading interest indicator and picture stories, which obtained a percentage of 86.67%. This percentage indicates the category of